Diseño De Una Metodología Para La Optimización Del Proceso De Gerenciamiento De Proyectos En La Compañía Mas Energía SAS (2021)
This project aims to design a methodology that allows the company MAS ENERGIA SAS to apply an improvement in its engineering process by building its own project execution system based on traditional and agile methodologies such as PMBOK, PRINCE2 and SCRUM, applying quality concepts of ISO 21500: 2013 that improve the performance of resources and utilities in practice. For the design of this methodology, the observation of natural phenomena that occurred during the execution of different projects in field diaries was used, likewise a check list was prepared based on the criteria of the selected methodologies which was applied to a sample, information that was analyzed with the help of statistical tools which allowed an initial diagnosis to be made; From the information obtained, a design was made that proposes five basic stages: initiation, planning, execution, monitoring - control and closure, which are described in technical sheets that include objective, description, activities, participants and necessary resources of each one.